Perbandingan Efektivitas Paracetamol dan Ibuprofen untuk Terapi Penurun Demam pada Usia 6 Bulan sampai 18 Tahun di RSUD Kota Depok periode Juni 2023 sampai Juni 2024 - Rahayu, Mustika; Ambarsari, Niati; Fadilah, Nur (Politeknik Tiara Bunda, 2024)
Fever has been noted as a precursor or characteristic of the disease. Conditions that aggravate fever often result in therapeutic failure or a poor prognosis. This study aims to analyze the comparison of single therapy administration of Paracetamol, Ibuprofen and a combination of both in treating fever and/or pain in patients aged 6 months to 18 years. The results of the study showed that using Ibuprofen alone was better at reducing fever in the first 4 hours than Paracetamol alone, however, the combination therapy of the two was not much different from using Ibuprofen alone. To treat pain accompanied by fever, using Ibuprofen alone has been proven to provide a longer pain-free period compared to using Paracetamol alone, and the combination of the two is not much different from Ibuprofen